Exploring Content Creator’s Digital Identity Formation via Social Media Platforms - Benitez, Krissaquel Sistona; Macaraeg, Rebecca Joyce Trinidad; Yatco, Eleri Morene Cariño; Escobin, Ann Valerae; Pablayan, Shania Faye Nicole; Dominguez, Jemerson (Journal of Health and Behavioral Science, 2024)
This research examines digital identity formation among Filipino content creators on TikTok. The participants were 21 Filipino content creators, aged 20 to 46 and were interviewed through an online platform. Utilizing a Grounded Theory approach, it aims to generate insights into how content creators navigate digital spaces, shaping their digital identity and fostering connections. The study identifies three selective codes : Identity Construction, Embodiment of Online Persona, and Building Social Currency, each encompassing various sub-themes that underscore the strategic and dynamic nature of digital identity formation. The research also presents five distinct phases in content creators' digital identity formation on social media platforms: Exploration, Uncovering Niche, Targeted Audience, Publishing Contents, and Integration of Digital Identity, elucidating the progression from initial curiosity to the establishment of a digital identity.Keywords: Digital Identity; Social Media; Content Creators; Tiktok